Which statement(s) are true based on the pythagorean identities? sine squared (theta) = 1 cosine squared theta 1 = secant squared theta minus tangent squared theta cotangent squared theta = cosecant squared theta minus 1 1 minus tangent squared theta = negative secant squared theta negative cosine squared theta = sine squared theta minus 1

Pythagoreanidentities is cotangent-squared of theta –cosecant-squared of theta = -1.## Why is the equation above true?

correct.cotangent-squared of theta – cosecant-squared of theta = -1.Pythagoreanfrom